Mekanisme Pertahanan Ego Anggota Punk dalam Menghadapi Prasangka Sosial - Izzul Jinan Isna Alluza; Fattah Hanurawan; Nur Eva (Universitas Negeri Malang, 2021)
Abstract: The method used in this study is qualitative research with phenomenological research types. Data collection tools in this study were interviews and open questionnaires. Type checking the validity of the data in this study using interpretative validation. Results of the research are the ego defense mechanisms used by research subjects in the face of social prejudice. There are 3 categories and 5 types of ego defense mechanisms. The third category is the primitive ego defense mechanism, less primitive ego defense mechanisms, and the mature ego defense mechanisms. In the category of primitive ego defense mechanisms, there is one kind of ego defense mechanism of the type of regression. While less primitive, there are two types of ego defense mechanisms, namely repression and displacement. And in the adult category there are two types of ego defense mechanisms, namely sublimation and assertiveness. Keywords: ego defense mechanisms; social prejudice Abstrak: Penelitian ini bertujuan untuk mengetahui mekanisme pertahanan ego apa yang diterapkan anggota kelompok punk di ITN dalam menghadapi prasangka sosial. Metode penelitian yang digunakan adalah penelitian kualitatif fenomenologi. Pengumpulan data dalam penelitian ini menggunakan wawancara dan kuesioner terbuka. Pengecekan keabsahan data menggunakan validasi interpretatif. Hasil penelitian yang diperoleh adalah mekanisme pertahanan ego yang digunakan oleh subjek penelitian dalam menghadapi prasangka sosial yakni: a. Mekanisme pertahanan ego primitif yaitu mekanisme pertahanan ego jenis regresi, b. Mekanisme pertahanan ego kurang primitif yang meliputi represi dan displacement, c. Mekanisme pertahanan ego dewasa meliputi mekanisme pertahanan ego sublimasi dan assertiveness. Kata kunci: mekanisme pertahanan ego; prasangka sosial